Achieving high thermoelectric performance through carrier concentration optimization and energy filtering in Cu3SbSe4-based materials - Sitong Wei; Boyi Wang; Zipei Zhang; Wenhao Li; Lu Yu; Shikai Wei; Zhen Ji; Weiyu Song; Shuqi Zheng (Journal of Materiomics, 2022)
The previous works commonly adjust the carrier concentration through acceptor doping, but at the same time, the decrease of the Seebeck coefficient limits the further improvement of electrical properties in Cu3SbSe4-based materials. In this work, a microwave-assisted hydrothermal synthesis method was used to synthesize Cu3SbSe4/TiO2 hollow microspheres. Part of TiO2 participates in the reaction, replaces the Sb site of Cu3SbSe4 to form holes, and the rest is dispersed in the matrix in the form of the second phase. The first-principles calculations reveal that the doping of Ti significantly changes the band structure and phonon spectrum, thereby regulating carrier concentration while increasing phonon scattering. In addition, experimental results show that the energy filtering effect generated by the extra-mixed TiO2 nano particles, which suppresses the decrease of Seebeck coefficient by acceptor doping. Consequently, the highest average power factor 897.5 μW m−1 K−2 and the zT peak value of 0.70 can be obtained in Cu3SbSe4/6%TiO2 sample at 298–623 K. This work provides a new sight to improve the thermoelectric properties in Cu3SbSe4 through carrier concentration regulation and nano-phase composition.